Fostering creativity, advanced technology, and personal growth: The impact of a magic-themed learning experience in primary education - Elena Vercher Ribis (Revista Catalana de Pedagogia)
This research explores the effects of a magic-themed, project-based learning approach on creativity, digital skills, personal growth, and emotional intelligence among 63 primary school students at Escola Sant Jordi. Students aged 8-10 participated in a series of activities where they created digital spells, virtual worlds, and interactive objects using tools like CoSpaces, Tinkercad, and micro:bit, integrating augmented reality and 3D printing. With a focus on incorporating technology into the learning process, the study investigates how imaginative themes can foster student engagement and development in these key areas.